Attitude of School Teachers towards Inclusive Education With Respect to Gender and Management - Leinak , Shamla; Nath Babu, M. Rajendra (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Inclusive Education has become a fundamental human right today. It has evolved as a movement to challenge all exclusionary policies and practices and has gained momentum over the past decade. The main purpose of the study is to know the attitude of school teachers towards inclusive education with respect to gender and management. For the purpose of the study, the investigators selected 200 samples of school teachers by using Simple Random Sampling technique from 15 schools. Sentiments, Attitude and Concerns about Inclusive Education Scale-Revised’ (SACIES-R) questionnaire was used for the present study by the investigators. Mean, SD, t-test were used to analyze the data. The result shows that male teachers in schools had more positive attitude towards inclusive education as compared to female teachers.